# Answer on Algebra Question for Andy

Question #9918

Multiply (x^9+3)^2

Expert's answer

The well-known formula for squaring a sum of two numbers or terms is

[img width=196,height=40]http://images.planetmath.org/cache/objects/7427/js/img1.png[/img]

So due to it we obtain

(x^9+3)^2=x^{18}+6x^{9}+9

[img width=196,height=40]http://images.planetmath.org/cache/objects/7427/js/img1.png[/img]

So due to it we obtain

(x^9+3)^2=x^{18}+6x^{9}+9

Need a fast expert's response?

Submit orderand get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

## Comments

## Leave a comment